Odpowiedź :
Odpowiedź:
[tex]\frac{1}{2}[/tex]([tex]\frac{2}{3}[/tex]([tex]\frac{3}{4}[/tex]x-1))=
[tex]\frac{1}{2}[/tex]([tex]\frac{2}{4}[/tex]x-[tex]\frac{2}{3}[/tex])=[tex]\frac{3}{4}[/tex]([tex]\frac{1}{3}[/tex]x+
[tex]\frac{1}{4}[/tex]x-[tex]\frac{1}{3}[/tex]=
[tex]\frac{1}{4}[/tex]x-
0≠[tex]\frac{5}{6}[/tex]
L≠P
Szczegółowe wyjaśnienie:
Równanie nie ma rozwiązania
b)
[tex]\frac{1}{2}(\frac{2}{3}(\frac{3}{4}x - 1) )=\frac{3}{4}(\frac{2}{3}(\frac{1}{2}x}+1))\\\\\frac{1}{3}(\frac{3}{4}x-1) = \frac{1}{2}(\frac{1}{2}x+1)\\\\\frac{1}{4}x -\frac{1}{3} = \frac{1}{4}x + \frac{1}{2}\\\\\frac{1}{4}x -\frac{2}{6} = \frac{1}{4}x + \frac{3}{6}\\\\\frac{1}{4}x -\frac{1}{4}x = \frac{3}{6}+\frac{2}{6}\\\\0 = \frac{5}{6}, \ sprzecznosc, \ brak \ rozwiazania\\\\0 \neq \frac{5}{6}[/tex]